Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Cerita SPLTV Ditinjau Dari Motivasi Belajar - Nopiana, Rida; Ratnaningsih, Nani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2023)
Math word problems are very important for students to understand, because math word problems are related to life. However, there are still many students who have difficulty in solving math word problems. Different levels of learning motivation can affect students' mistakes in solving math word problems. This study used descriptive qualitative method. The subjects of this study were 18 students of class XI IPS 3 MAN 5 Tasikmalaya and 3 subjects were selected by purposive selection taking into account the results of the questionnaire scores from each category and the number of errors. The results of this study, subjects with high motivation categories only made 2 mistakes only in the type of comprehension error, namely not writing down what was known and not writing down what was asked in the problem. Subjects in the category of moderate motivation made 5 errors in the types of comprehension errors (Comprehension Error), Skill Error (Process Skill Error), and final writing error (Encoding Error), namely not writing down what is known, not writing down what is being asked, not writing examples. , wrong in calculating, and wrong in writing the final conclusion. Whereas subjects with low motivation categories made 7 mistakes in all types of errors, namely not writing down what was known, not writing down what was being asked, not writing examples, wrongly compiling the equation of the problem, not continuing the solving process, wrong in doing the calculations, and not write a final conclusion. It is recommended for further researchers to conduct interviews with research subjects to obtain more in-depth information.